Physico-Chemical Studies of Complexes of Trivalent Lanthanide Metal ions with 2-hydroxy phynel hydrazo dimedone in Ethanol-Water Mixed Solvent System - Mohamed Elbakush (The Libyan Journal of Science, 2022)
The organic ligand was prepared by diazonium coupling of 2-hydroxy aniline with dimedone. Potentiometric titration used to calculate dissociation constants of this ligand in mixed solvent system (75% methanol-water) at different temperatures, the values were used in calculating the stability constants for this ligand with trivalent lanthanide metal ions in mixed solvents and constant ionic strength of 0.1M solution sodium nitrite. The effect of temperature on dissociation constants of the organic ligand and formation constants of the complexes also studied. Thermodynamic parameters were calculated using Vant-Hoff equation.